Zn and Cu in green mussel (Perna Viridis) and sea water of Pantai Lido-Pendas - Nurul Hainurnisa Mazlan, 1988-; Jafariah Jaafar; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010